1993
DOI: 10.1007/bf01744743
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological intervention for renal protection during cardiopulmonary bypass

Abstract: The possibility of minimizing organ damage following cardiopulmonary bypass (CPB) was examined. In the control group, n = 21, upon completion of CPB, elevation of the lysosomal enzyme beta-glucuronidase, which is a sensitive indicator of cellular damage, was affected by the concentration of granulocyte elastase (r = 0.59) or the endothelial-derived constricting factor, endothelin, (r = 0.8). Renal damage, which was detected by an increase in renal tubular enzymes (N-acetyl-beta-D-glucosaminidase and gamma-glut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 28 publications
0
26
0
3
Order By: Relevance
“…Boldt et al [13] reported that kidney damage was significantly more severe in patients with CPB time >90 min compared to those with CPB time <70 min. Renal injury may be caused by the production of free radicals, hydroxyl radicals, endothelin, free plasma hemoglobin, and elastase during CPB [14,15]. Non-pulsatile flow, renal hypoperfusion, and hypothermia were reported to show adverse effects on renal function [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Boldt et al [13] reported that kidney damage was significantly more severe in patients with CPB time >90 min compared to those with CPB time <70 min. Renal injury may be caused by the production of free radicals, hydroxyl radicals, endothelin, free plasma hemoglobin, and elastase during CPB [14,15]. Non-pulsatile flow, renal hypoperfusion, and hypothermia were reported to show adverse effects on renal function [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…The primary therapeutic effect in these disease states is protection of the kidneys from Hb-induced toxicity. 87 Thus far, no therapeutic experience exists for Hpx in a clinical setting. However, several United States-and European-based pharmaceutical companies have commenced development projects to fractionate Hp and Hpx from human plasma for use as therapeutics during hemolytic diseases.…”
Section: Conclusion: Is There An Unmet Need For Scavenger Protein-basmentioning
confidence: 99%
“…Ulinastatin (UTI; urinary trypsin inhibitor) is a Kunitz-type protease inhibitor that inhibits the activity or release of lysosomal enzymes such as elastase and catepsin G [5,6]. It has been reported to help protect against shock and operative stress [7-10] and suppress the deterioration of renal function associated with surgical procedures, chemotherapy, and various types of shock [11][12][13]. However, the effects of UTI on energy metabolism and intracellular Na ϩ levels have not been fully investigated, and its mechanisms for protecting against renal ischemia have not yet been clarified.…”
mentioning
confidence: 99%